Volatile Organic Compounds and Dimethyl Methyl Phosphonate (DMMP) Sensing Properties of the Metal Oxide Functionalized QCM Transducers at Room Temperature - Kösemen, Arif; Öztürk, Sadullah; Şen, Zafer; Alpaslan Kösemen, Zühal; Harbeck, Mika; Öztürk, Zafer Ziya (The Electrochemical Society, 2017)
ZnO nanorods were synthesized directly on the mass sensitive transducer elements, namely the quartz crystal microbalance (QCM), by electrochemical deposition techniques. Besides, vanadium pentaoxide (V2O5) thin films were evaporated on the ZnO nanorods using a thermal evaporation system. The fabricated chemical gas sensors were exposed to different levels of various volatile organic compounds (VOCs). The VOCs sensing measurements were realized at room temperature. The application of an additional V2O5 layer on the ZnO nanorods was found to improve the sensing performance of the nanorods. The highest responses were obtained for the analyte DMMP and the DMMP sensitivities of the sensors are at least three times higher than the sensitivities for the other tested VOCs. ZnO nanorods are considered excellent sensing materials on the QCM allowing selective detection of DMMP and other analytes at room temperature.